2020
DOI: 10.3390/nu12041202
|View full text |Cite
|
Sign up to set email alerts
|

Monobutyrin and Monovalerin Affect Brain Short-Chain Fatty Acid Profiles and Tight-Junction Protein Expression in ApoE-Knockout Rats Fed High-Fat Diets

Abstract: Monobutyrin (MB) and monovalerin (MV), esters of short-chain fatty acids (SCFAs), have previously been shown to reduce liver cholesterol and inflammation in conventional rats fed high-fat diets. This study explored the potential effects of MB and MV in hypercholesterolemic apolipoprotein E-knockout (ApoE-/-) rats. ApoE-/- rats were fed three high-fat (HF) diets, pure or supplemented with MB or MV (1%), for 5 weeks. One group of conventional rats (C) was also fed the pure high-fat diet and another group of ApoE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…SCFAs are products of gut microbiota and play considerable roles in colonic health and integrity. SCFAs mainly consistent of acetate, butyrate, and propionate, which may affect the expression of TJ proteins and inflammatory factors, and playing an important role in promoting epithelial barrier function and wound healing 21,28 . Therefore, we speculated that TDEP may also affect the expression of SCFAs in feces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCFAs are products of gut microbiota and play considerable roles in colonic health and integrity. SCFAs mainly consistent of acetate, butyrate, and propionate, which may affect the expression of TJ proteins and inflammatory factors, and playing an important role in promoting epithelial barrier function and wound healing 21,28 . Therefore, we speculated that TDEP may also affect the expression of SCFAs in feces.…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs mainly consistent of acetate, butyrate, and propionate, which may affect the expression of TJ proteins and inflammatory factors, and playing an important role in promoting epithelial barrier function and wound healing. 21 , 28 Therefore, we speculated that TDEP may also affect the expression of SCFAs in feces. We detected the SCFAs by HPLC, and found that the content of all the SCFAs was decreased by TDEP administration in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Mulder et al showed a dramatically increased BBB permeability in adult ApoE–/– mice with chronic HFD intake ( 74 ), whereas Bai et al demonstrated that the consumption of an HFD elevated levels of GFAP, pro-inflammatory and pro-apoptotic factors in the cortex and hippocampus of 20-week-old male ApoE–/– mice ( 75 ). Another work suggests that 5-week feeding of ApoE-deficient rats with an HFD upregulated IL-1β and decreased the expression of occludin in the brain (signs of neuroinflammatory reaction), compared with an LFD ( 76 ). In contrast, there is evidence indicating the beneficial effect of a high-fat/high-cholesterol diet on the expression of BDNF and TrkB mRNAs in the hippocampus of 20-week-old ApoE–/– mice, which is related to improved synaptic plasticity ( 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tight junction proteins play an important role in the barrier function of the duodenal mucosa, and tight junction proteins such as ZO-1 and CX43 are commonly used as indicators to assess the barrier function and permeability function of the intestinal epithelial mucosa ( Oshima and Miwa, 2016 ). Studies show that monobutyric acid and monovaleric acid in ScFAs can upregulate the expression of the tight junction protein ZO-1 and thus protect the intestinal mucosal barrier ( Nguyen et al, 2020 ). Intestinal epithelial cells are an important component of the intestinal mucosal barrier and are differentiated from stem cells at the base of the intestinal mucosal crypts, and the maintenance and repair of the intestinal mucosal barrier depends on the normal proliferation and differentiation of these stem cells ( You et al, 2021 ).…”
Section: Possible Mechanisms Of Fd Due To the Dysbiosis Of Gastrointe...mentioning
confidence: 99%